ANALYSIS OF THE EFFECT OF SERVICE QUALITY AND BRAND IMAGE ON PURCHASING DECISIONS: CASE STUDY OF K-24 PHARMACY - Ibrahim, Sholeh (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine the effect of service quality and brand image on purchasing decisions for K-24 pharmacies in Surabaya. Method: The type of research used in this study is quantitative. In particular, sampling techniques are often used to collect random data with data analysis instruments studied, which have quantitative statistical objectives to test hypotheses. Results: The effect of service quality variables on purchasing decisions has a t-value of 2.706 and a significant value of 0.009. This means that the service quality variable has a significant influence on the purchasing decision variable. The influence of the brand image variable on purchasing decisions has a t-value of 3.847 and a calculated value of 0.000. This means that the brand image variable has a significant influence on the purchasing decision variable. Based on the research results, it shows that the service quality variable has a significant influence on the purchasing decision variable. Then, the brand image variable has a significant influence on the purchasing decision variable. Novelty: Based on the research results above, the authors conclude that the service quality variable (X1) and the brand image variable (X2) have a simultaneous influence on the purchasing decision variable (Y).